Problematika Guru Pendidikan Agama Islam Berbasis Komunitas dalam Persiapan Implementasi Kurikulum Merdeka di MTs Negeri Jayawijaya Papua - Ubaidillah, A. (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
The independent curriculum is one of the government's efforts to improve human resources through education. The purpose of this study is to determine the preparation for the implementation of an independent curriculum in rural Papua, especially the problems faced by community-based PAI teachers at MTs Negeri Jayawijaya. This research uses a qualitative descriptive method that describes the reality obtained during the research so that it becomes information that is easy to understand and data that is positively useful in the world of education. The results showed that the preparation for the implementation of the independent curriculum at MTs Negeri Jayawijaya experienced obstacles due to students who had minimal learning experience, low student learning awareness, and unstable internet networks.